Study on Screening Tests among the Blood Donors in Dhaka Medical College Hospital, Bangladesh (Journal of Dhaka Medical College, 2010)
Context: Most deaths caused by transfusion worldwide is due to transmission of infectious agents like Virus, Bacteria and Protozoa. The risk of disease transmission increases many fold if blood donor selection is inappropriate (such as blood from professional donor) and testing of all blood for transfusion is inadequate. Methods: The study was carried out in transfusion Medicine department of Dhaka Medical College Hospital from January to December 2009 to see the prevalence of HBV, HCV, HIV, Treponema pallidum and Malarial parasite among the donor. Results: The study was carried out on 21448 donors, among whom 4464 (20.81%) were voluntary and 16984 (79.19%) were relative donors. Among 21448 donors, 21081 (98.29%) were selected and 367 (1.71%) were rejected. Out of 21081 selected donors 4406 (20.9%) were voluntary donor and 16675 (79.1%) were relative donor. Out of 367 rejected 58 (15.8%) were voluntary and 309 (84.2%) were relative donor. On analyzing the 367 rejected cases, HBsAg positive 297 (80.93%), Anti HCV positive 38 (10.35%), Malarial Parasite positive 23 (6.27%), Treponema pallidum positive 9 (2.45%) and none found positive for HIV. Key words: Blood donor; Voluntary donor; Relative donor; Screening. DOI: 10.3329/jdmc.v19i1.6245 J Dhaka Med Coll. 2010; 19(1) : 16-18.